NEPAD and Foreign Direct Investment in Africa (Journal of Management and Social Sciences, 2016)
The New Partnership for Africa's Development is a pledge by African Leaders based on a common vision and a firm, shared conviction that they have a pressing duty to eradicate poverty and place their countries, both individually and collectively on a path of sustainable growth and development and to participate actively in the world economy and politics (NEPAD, 2001). The paper uses the political economy theory to examine the philosophy of the New Partnership for Africa's Development and the policy has been able to attract foreign direct investment. The research relies on secondary sources of data for the purpose of evaluating the successes and failures of NEPAD. The paper recommends that regional integration be strengthen to enhance economy interaction among African States and conflict prevent mechanism be strengthen to reduce persistence conflict in Africa, to encourage foreign investment in the region. KeywordsNEPAD, Foreign Direct Investment, development, poverty, underdevelopment